Antihyperurisemia activity of water extract of black seed (Coleus ambonicusLour) in balb-c mice and its standardization - Andi Suhendi; Nurcahyanti .; Muhtadi .; EM Sutrisna (Indonesian Journal of Pharmacy, 2011)
Effect  of  water  extract  of  black  seed  on  uric  acid  metabolism  in hyperuricemia mice models were studied. The influence of water extract of black seed  on  uric  acid  biosynthesis  was  xamined  using  mice  treated  by  250  mg/ body  weight  potassium  oxonate  intra  peritoneal.  The result  showed  that  water extract of black seed (200 mg/kg body weight, per oral) have a significant effect in reduction in plasma uric acid levels in comparison to negative control, but less active  than  positive  control  (allopurinol).  The  levels  of  uric  acid  in  mice  plasma for negative control, black seed extract and positive control were 3.100 ± 0.346 mg/dL,  0.200  ±  0.100  mg/dL  dan  1.200  ±  0.561  mg/dL,  respectively.  The standardization  performed  by  determined  specific  and  non  specific  parameters based  on  National  Bureau  of  Food  and  Drug,  Republic of  Indonesia.  Specific parameters  of  water  extract  of  black  seed  are  phenolic  content,  and  flavonoid content  are  0.664  ±  0.035  %  and  0.400  ±  0.018  %,  respectively.  Non  specific parameters of water extract of black seed are loss of weight, water content, ash content,  ash  insoluble  acid  content,  heavy  metals  contamination  (Pb  and  Cd), and  aflatoxin  residue  are  14.93-14.99%,  6.09-7.89%, 7.12-7.49%,  5.20-6.66%, 6.405 +0.211 ppm, 0.0096 +0, not detected, respectively.Key words: antihyperuricemia effect, water extract of black seed, standardization